Letjaščaja ikona – semantika i funkcii odnoj legendyThe Flying Icon – the Semantic and the Functions of One Legend - Anastasova, Ekaterina (Studia mythologica Slavica, 2007)
<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-ansi-language: EN-US; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">In the article is analyzed the story of the “flying” icons from the Nessebar church of “The Assumption of the Holy Virgin”. These legends describe the miracles made by the icon of the Holy Virgin – the Black (Mad) Mary. The miracles comprise its “flying” to the Greek community in Nessebar in the times of the Ottoman domination and its role in diverse historical trials. The legends of the “flying” icon of Nessebar appear as metaphorical readings of the intensive identification processes that have involved individuals and communities in transitional historical periods.